Costs comparison of treating diabetic macular edema with aflibercept, ranibizumab or dexamethasone at 1 year in France (INVICOST study). Issue 3 (May 2022) - Gascon, Pierre; Borget, Isabelle; Comet, Alban; Carton, Laurence; Matonti, Frédéric; Dupont-Benjamin, Laure
Purpose: INVICOST, a medico-economic analysis, compared costs of managing treatment-naive patients with diabetic macular edema (DME) receiving intravitreal injections (IVIs) of aflibercept (AFL), dexamethasone implant (DXI) or ranibizumab (RAN) over 1 year. Methods: Healthcare resource use and associated costs were estimated using individual patient data from INVICTUS, a prospective, open-label, monocentric study. Healthcare costs comprised direct medical costs such as drug acquisition and administration, consultations and ophthalmological procedures. Costs were assessed from the French National Health Insurance perspective using published national tariffs expressed in 2019 euros. Results: Of the 60 treated eyes, 48 had no treatment switch; 14 received AFL, 19 received DXI and 15 received RAN. AFL-treated eyes received an average of 6.5 IVIs, DXI-treated patients received 2 IVIs and RAN-treated received 6.8 IVIs. All treated eyes received an initial prescription for adjunctive ocular medications and 349 follow-up procedures were performed including an average of 3.9 optical coherence tomography and 3.2 retinography procedures per eye. Average total direct cost of per-eye treatment was €4516 (€1128–€8257). Average cost was €5782 for eyes treated with AFL, €2779 with DXI and €5536 with RAN. Drug therapy was the cost driver: €4394 (76%) for AFL, €1915 for DXI (69%) and €4268 (77%) for RAN. Conclusion: The difference in total treatment cost is largely explained by the significantly lower frequency of IVI and annual cost of therapy with DXI, compared with AFL and RAN. INVICOST is the first study comparing treatment costs with AFL, DXI and RAN in France in current clinical practice.